Weicao capsule ameliorates renal injury through increasing autophagy and NLRP3 degradation in UAN rats. (March 2018) - Hu, Jiacai; Wu, Hao; Wang, Daochun; Yang, Zhijie; Zhuang, Lihua; Yang, Na; Dong, Junjun
Highlights: Weicao inhibits NLRP3 inflammasome-derived inflammation. Weicao augments autophagy activity. Weicao exerts anti-proliferative and anti-apoptosis effects on NRK-52E in macrophages from UAN rats. Weicao exerts anti-inflammatory and renal-protective effect on UAN rats. Abstract: Uric acid nephropathy (UAN) is one of the most common metabolic diseases and leads to kidney damage. This study aimed to evaluate the effect of Weicao capsule on renal injury of UAN rats and to examine whether the mechanism was associated with induction of autophagy and degradation of nucleotide binding oligomerization domain (Nod)-like receptor (NLR) protein 3 (NLRP3) inflammasome. Sixty Sprague-Dawley rats were randomly allocated into 6 groups: Control, Model, Allopurinol, and Weicao (0.55/1.1/2.2 g/kg) group. The data showed activation of renal NLRP3 inflammasome in UAN rats, with elevation in serum levels of interleukin (IL)-1β and IL-18, and subsequent deterioration of renal injury. Fortunately, Weicao had a markedly therapeutic effect on UAN rats, including improving renal function-related indexes, ameliorating hyperuricemia-related inflammation, decreasing crystals in renal tissue and alleviating renal interstitial fibrosis. Additionally, Weicao exerted anti-proliferative and anti-apoptosis effects on rat renal tubular epithelial cell NRK-52E in macrophages from UAN rats. Our investigation into the mechanism revealed that Weicao suppressed the activated NLRP3 inflammasome. Furthermore, Weicao induced autophagy, as evidenced by a dose-dependent increase in levels of renal autophagy-related proteins in UAN rats. Moreover, autophagy inhibitor 3-MA and NLRP3 activator ATP blocked the effect of Weicao on autophagy induction and NLRP3 inflammasome degradation. In conclusion, Weicao had similar effects as allopurinol and exerted anti-inflammatory and renal-protective effect in a concentration-dependent manner in UAN rats, most likely through increasing autophagy and NLRP3 degradation. Our study provides new insight into the underlying mechanism of Weicao in the treatment of UAN.